2016
DOI: 10.1155/2016/4514687
|View full text |Cite
|
Sign up to set email alerts
|

Tea and RecurrentClostridium difficileInfection

Abstract: Background and Aims. Studies have shown effects of diet on gut microbiota. We aimed to identify foods associated with recurrent Clostridium difficile infection (CDI). Methods. In this cross-sectional survey, consecutive patients diagnosed with CDI were identified by electronic medical records. Colitis symptoms and positive Clostridium difficile assay were confirmed. Health-care onset-health-care facility associated CDI was excluded. Food surveys were mailed to 411 patients. Survey responses served as the prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…A recent retrospective clinical trial in C. diff patients (Veteran Administration hospitals) with recurrent infection who drank tea showed the possible antimicrobial effects of tea. It was suggested that tea in the gut of these patients may reduce the normal microbiome and provoke overgrowth of the facultative pathogens [70]. However, the low number of participants in this trial requires further in-depth investigations to confirm these findings.…”
Section: Tea Polyphenols and Possible Side Effectsmentioning
confidence: 84%
See 1 more Smart Citation
“…A recent retrospective clinical trial in C. diff patients (Veteran Administration hospitals) with recurrent infection who drank tea showed the possible antimicrobial effects of tea. It was suggested that tea in the gut of these patients may reduce the normal microbiome and provoke overgrowth of the facultative pathogens [70]. However, the low number of participants in this trial requires further in-depth investigations to confirm these findings.…”
Section: Tea Polyphenols and Possible Side Effectsmentioning
confidence: 84%
“…In the era of antibiotic resistance and the hospital superbug epidemic, the use of GrTPs as natural antimicrobial and antifungal agents is an attractive area to be explored. However, GrTPs natural antimicrobial status that possibly alters the gut microbiome may be perceived as an adverse effect with can support facultative C. diff in certain vulnerable populations [70]. These warnings against GrTP utilization requires further in-depth trials before any recommendations can be implemented.…”
Section: Discussionmentioning
confidence: 99%
“…70 It was suggested that tea in the gut of these patients may reduce the normal microbiome and provoke overgrowth of the facultative pathogens. 71 Therefore, EGCG is counter-regulated by the presence of iron and lipocalin 2. EGCG prevents the peroxidase-catalyzed reaction by reverting the reactive peroxidase heme (compound I: oxoiron) back to its native inactive ferric state, possibly via the exchange of electrons.…”
Section: Egcg and Its Possible Side Effectsmentioning
confidence: 99%
“…It is noteworthy that caffeine consumption has been specifically linked to an increase in sleep disturbances, characteristic of this population [ 161 ], as well as the presence of maladaptive behavior in children with ASD [ 162 ]. Furthermore, concerning the microbiota in individuals vulnerable to Clostridium difficile infections, an increased risk in such infections has been associated with tea consumption, as it disrupts the normal microbiome and promotes the overgrowth of facultative pathogens [ 163 ]. Tea consumption has also been identified as a risk factor for gastroesophageal reflux disease (GERD) [ 164 ], which is relevant considering that GERD is one of the gastrointestinal symptoms commonly described as ASD [ 165 ].…”
Section: Polyphenols As a Therapeutic Alternative To Asd: The Epigall...mentioning
confidence: 99%